Stories of the Buddha : Being Selections from Jātaka - Davids, C.A.F. Rhys, (Brill | Manohar Publishers & Distributors, 2024)
Jātakas is one of the three-fold Pali Buddhist Canon or Pitakas. It contains around 550 stories from previous births of Buddha, both in human and animal forms. This illustrates the spiritual practices, acts, qualities, and personality of Buddha. The Jātaka stories narrate how Buddha plays the role of an intermediator, and gives a happy ending. Jātakas also narrate how to achieve Buddha-hood and narrates the story within the framework of Karma and rebirth. Jātakas were translated into many modern European and Indic languages such as German, Hindi, etc. Stories of the Buddha contains 47 selected tales collected from the original Jātakas, translated into English to make the teachings of Buddha alive in the minds of modern readers and scholars associated with Buddhism.